Home Visit Sebagai Metode Pembelajaran Anak Usia Dini Pada Masa COVID-19 - Maila D.H. Rahiem; Amelia Novi (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2022)
The aim of this study was to investigate and assess parents' and teachers' views of the home-visiting program as a method of early childhood education during the COVID-19 outbreak. Exploratory qualitative research employed as methods of inquiry. Twelve resource persons were interviewed (3 teachers and 9 parents). The data revealed, parents and teachers perceive that using home visits has a number of benefits and drawbacks. The benefits are as follows: 1) more effective than online; 2) make learning materials easy for children to understand; 3) pique children's interest and excitement for learning; and 4) eliminate the need for parents to assist their children with their tasks. Meanwhile, the downsides include the following: 1) it was inconvenient for parents because they were needed to entertain teachers and other children; 2) some pupils couldn't study because home visits were far away from their homes.; 3) additional media and learning activities preparation; 4) additional time and energy was wasted; and 5) the risk of exposure to COVID-19 was increased. The researchers recommend that additional study be conducted with a larger and more diverse sample size in order to obtain a more complete picture of this issue. Keywords: COVID-19, early childhood learning, emergency remote learning, preschool, kindergarten References Aliyar, R., Gelli, A., & Hamdani, S. H. (2015). A review of nutritional guidelines and menu compositions for school feeding programs in 12 countries. Frontiers in Public Health, 3, 148. Anderson-McNamee, J. K., & Bailey, S. J. (2010). The importance of play in early childhood development. Montana State University Extention, 4(10), 1–4. Asanov, I., Flores, F., McKenzie, D., Mensmann, M., & Schulte, M. (2021). Remote-learning, time-use, and mental health of Ecuadorian high-school students during the COVID-19 quarantine. World Development, 138, 105225. Auger, K. A., Shah, S. S., Richardson, T., Hartley, D., Hall, M., Warniment, A., Timmons, K., Bosse, D., Ferris, S. A., Brady, P. W., Schondelmeyer, A. C., & Thomson, J. E. (2020). Association Between Statewide School Closure and COVID-19 Incidence and Mortality in the US. JAMA, 324(9), 859. https://doi.org/10.1001/jama.2020.14348 Azevedo, J. P., Hasan, A., Goldemberg, D., Geven, K., & Iqbal, S. A. (2021). Simulating the potential impacts of COVID-19 school closures on schooling and learning outcomes: A set of global estimates. The World Bank Research Observer, 36(1), 1–40. Azevedo, J. P., Hasan, A., Goldemberg, D., Iqbal, S. A., & Geven, K. (2020). Simulating the Potential Impacts of COVID-19 School Closures on Schooling and Learning Outcomes: A Set of Global Estimates. The World Bank. https://doi.org/10.1596/1813-9450-9284 Baker, J. (2020). Experts call for major intervention to help struggling students. Available On-Line at Https://Www. Smh. Com. Au/National/Experts-Call-for-Major-Intervention-to-Help-Strugglingstudents-20200519-P54uii. Html. Briscese, G., Lacetera, N., Macis, M., & Tonin, M. (2020). Compliance with COVID-19 Social-Distancing Measures in Italy: The Role of Expectations and Duration. https://doi.org/10.3386/w26916 Budianti, A., & Melati, P. A. (2020). Implementasi Kunjungan Rumah Dalam Pembelajaran Pada Masa Pandemi. Academica: Journal of Multidisciplinary Studies, 4(2), 267–278. Chatterji, P., & Li, Y. (2021). Effects of COVID-19 on school enrollment. Economics of Education Review, 83, 102128. Chaudron, S., Beutel, M. E., Donoso Navarrete, V., Dreier, M., Fletcher-Watson, B., Heikkilä, A. S., Kontríková, V., Korkeamäki, R. v, Livingstone, S., & Marsh, J. (2015). Young children (0-8) and digital technology: A qualitative exploratory study across seven countries. JRC; ISPRA, Italy. Commodari, E. (2013). Preschool teacher attachment, school readiness and risk of learning difficulties. Early Childhood Research Quarterly, 28(1), 123–133. https://doi.org/https://doi.org/10.1016/j.ecresq.2012.03.004 Cooper, D. R., Schindler, P. S., & Sun, J. (2006). Business research methods (Vol. 9). Mcgraw-hill New York. Dayal, H. C., & Tiko, L. (2020). When are we going to have the real school? A case study of early childhood education and care teachers’ experiences surrounding education during the COVID-19 pandemic. Australasian Journal of Early Childhood, 45(4), 336–347. DeMulder, E. K., Denham, S., Schmidt, M., & Mitchell, J. (2000). Q-sort assessment of attachment security during the preschool years: links from home to school. Developmental Psychology, 36(2), 274. Dias, M. J. A., Almodóvar, M., Atiles, J. T., Vargas, A. C., & Zúñiga León, I. M. (2020). Rising to the Challenge: Innovative early childhood teachers adapt to the COVID-19 era. Childhood Education, 96(6), 38–45. https://doi.org/10.1080/00094056.2020.1846385 Dikti. (2018). Indonesia Higher Education Statistical Year Book 2018 (Vol. 15, Issue 21). https://doi.org/10.1002/chem.200802548 Dini, J. (2021). Problematika pembelajaran daring dan luring anak usia dini bagi guru dan orang tua di masa pandemi Covid 19. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 5(2), 1825–1836. Dong, C., Cao, S., & Li, H. (2020). Young children’s online learning during COVID-19 pandemic: Chinese parents’ beliefs and attitudes. Children and Youth Services Review, 118, 105440. Dwita, K. D., Anggraeni, A. I., & Haryadi, H. (2018). Pengaruh home visit dan motivasi belajar terhadap hasil belajar siswa di SDIT Harapan Bunda Purwokerto. Jurnal Ekonomi, Bisnis, Dan Akuntansi, 20(1) . Earn, D. J. D. (2012). Effects of School Closure on Incidence of Pandemic Influenza in Alberta, Canada. Annals of Internal Medicine, 156(3), 173. https://doi.org/10.7326/0003-4819-156-3-201202070-00005 FAIZAH, A. B., Sunaryo, I., & AUD, M. P. (2021). Efektivitas Pembelajaran Home Visit Pada Pendidikan Aud Dimasa Pandemi Covid 19 Di TK IT Khoiruummah Sukoharjo Tahun Ajaran 2020-2021. Universitas Muhammadiyah Surakarta. Filmer, D., Rogers, H., Angrist, N., & Sabarwal, S. (2020). Learning-adjusted years of schooling (LAYS): Defining a new macro measure of education. Economics of Education Review, 77, 101971. Fumanelli, L., Ajelli, M., Merler, S., Ferguson, N. M., & Cauchemez, S. (2016). Model-Based Comprehensive Analysis of School Closure Policies for Mitigating Influenza Epidemics and Pandemics. PLOS Computational Biology, 12(1), e1004681. https://doi.org/10.1371/journal.pcbi.1004681 Grek, S., & Landri, P. (2021). Education in Europe and the COVID-19 Pandemic. In European Educational Research Journal (Vol. 20, Issue 4, pp. 393–402). SAGE Publications Sage UK: London, England. Herrenkohl, T. I., Scott, D., Higgins, D. J., Klika, J. B., & Lonne, B. (2021). How COVID-19 is placing vulnerable children at risk and why we need a different approach to child welfare. Child Maltreatment, 26(1), 9–16. Ibda, H., & Laeli, D. N. (2021). Hasil Belajar Siswa Saat Pandemi Covid-19 Melalui Home Visit Studi di MI Salafiyah Kranggan. At-Thullab: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 5(1), 12–22. Kakwani, N. (1980). On a class of poverty measures. Econometrica: Journal of the Econometric Society, 437–446. Kangas, J., Harju-Luukkainen, H., Brotherus, A., Kuusisto, A., & Gearon, L. (2019). Playing to learn in Finland: Early childhood curricular and operational context. Policification of Early Childhood Education and Care Early Childhood Education in the 21st Century Volume III. Katz, C., & Fallon, B. (2021). Protecting children from maltreatment during COVID-19: Struggling to see children and their families through the lockdowns. Child Abuse & Neglect. Kim, J. (2020). Learning and teaching online during Covid-19: Experiences of student teachers in an early childhood education practicum. International Journal of Early Childhood, 52(2), 145–158. Lau, E. Y. H., & Lee, K. (2021). Parents’ Views on Young Children’s Distance Learning and Screen Time During COVID-19 Class Suspension in Hong Kong. Early Education and Development, 32(6), 863–880. https://doi.org/10.1080/10409289.2020.1843925 Lennox, J., Reuge, N., & Benavides, F. (2021). UNICEF’s lessons learned from the education response to the COVID-19 crisis and reflections on the implications for education policy. International Journal of Educational Development, 85, 102429. Listyawati, B. W., Hanif, M., & Anggraheni, I. (2021). Problematika Pembelajaran Home Visit di Raudhatul Athfal Darul Falah Karangploso Malang. Jurnal Dewantara, 3(1), 76–81. Malhotra, A., & Elnakib, S. (2021). 20 years of the evidence base on what works to prevent child marriage: A systematic review. Journal of Adolescent Health, 68(5), 847–862. Mashburn, A. J., Pianta, R. C., Hamre, B. K., Downer, J. T., Barbarin, O. A., Bryant, D., Burchinal, M., Early, D. M., & Howes, C. (2008). Measures of classroom quality in prekindergarten and children’s development of academic, language, and social skills. Child Development, 79(3), 732–749. Mastoah, I., & MS, Z. (2020). Kendala Orang Tua Dalam Mendampingi Anak Belajar Pada Masa Covid 19 Di Kota Serang. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(2), 121–128. Mayurasakorn, K., Pinsawas, B., Mongkolsucharitkul, P., Sranacharoenpong, K., & Damapong, S. (2020). School closure, COVID‐19 and lunch programme: Unprecedented undernutrition crisis in low‐middle income countries. Journal of Paediatrics and Child Health, 56(7), 1013–1017. Miles, M. B., Huberman, M. a, & Saldana, J. (2014). Drawing and Verying Conclusions. Qualitative Data Analysis: A Methods Sourcebook. https://doi.org/January 11, 2016 Miller, J. C., Danon, L., O’Hagan, J. J., Goldstein, E., Lajous, M., & Lipsitch, M. (2010). Student Behavior during a School Closure Caused by Pandemic Influenza A/H1N1. PLoS ONE, 5(5), e10425. https://doi.org/10.1371/journal.pone.0010425 Ministry of Education and Culture. (2019). The 2019/2020 Early Childhood Education Statis. https://doi.org/10.1017/CBO9781107415324.004 Ministry of Education and Culture. (2020a). 2019/2020 Junior High School Statistic. http://statistik.data.kemdikbud.go.id/index.php/page/smp Ministry of Education and Culture. (2020b). 2019/2020 Primary Education Statistics. http://statistik.data.kemdikbud.go.id/index.php/page/sd Ministry of Education and Culture. (2020c). 2019/2020 Senior High School Statistic. http://statistik.data.kemdikbud.go.id/index.php/page/sma Ministry of Education and Culture. (2020d). 2019/2020 Vocational School Statistic. http://statistik.data.kemdikbud.go.id/index.php/page/smk Misirli, O., & Ergulec, F. (2021). Emergency remote teaching during the COVID-19 pandemic: Parents experiences and perspectives. Education and Information Technologies, 26(6), 6699–6718. Mohsi, M. (2019). Langghar, Kophung Dan Bhaqaf Konservasi Kebudayaan Khazanah Keislaman Madura. Sabda: Jurnal Kajian Kebudayaan, 14(1), 14–20. Mokoginta, L., & Nurdiyani, N. (2020). Program Home Visit di Pos-PAUD Bintang Kecil, Semarang: Solusi Menaati Aturan Physical Distancing. E-Prosiding Pascasarjana Universitas Negeri Gorontalo, 43–48. Mulyaningsih, E., & Iskandar, R. (2021). Efektivitas Belajar Anak Usia Dini pada PAUD Miftahul Ulum di Masa Pandemi COVID-19. Jurnal Pendidikan Indonesia, 2(9), 1512–1521. Munastiwi, E. (2020). Colorful Online Learning Problem of Early Childhood Education During the Covid-19 Pandemic. Al-Ta Lim Journal, 27(3), 227–235. Munastiwi, E., & Puryono, S. (2021). Unprepared management decreases education performance in kindergartens during Covid-19 pandemic. Heliyon, 7(5), e07138. https://doi.org/https://doi.org/10.1016/j.heliyon.2021.e07138 Nasution, S. T., & Sutapa, P. (2020). Strategi Guru dalam Menstimulasi Keterampilan Motorik AUD Pada Era Pandemi Covid 19. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 5(2), 1313–1324. Nguyen, L. H. (2021). Calculating the impact of COVID-19 pandemic on child abuse and neglect in the US. Child Abuse & Neglect, 118, 105136. Nilsson, M., Ferholt, B., & Lecusay, R. (2018). ‘The playing-exploring child’: Reconceptualizing the relationship between play and learning in early childhood education. Contemporary Issues in Early Childhood, 19(3), 231–245. Nirmala, B., & Annuar, H. (2020). Home Visit: Strategi PAUD dari Rumah bagi Guru di Daerah 3T pada Masa Pandemi Covid-19. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 5(2), 1052–1062. Nofianti, R. (2020). Peran Orangtua Dalam Pendampingan Pembelajaran Daring Anak Usia Dini di Masa Pandemik Covid 19 Di Tk Islam Ibnu Qoyyim. Jurnal Abdi Ilmu, 13(2), 19–30. Nurrahmah, N. (2020). Tari Paddupa Khas Masyarakat Suku Bugis Makassar dalam Penyambutan Tamu (Tinjaun Nilai-Nilai Budaya Islam). Universitas Islam Negeri Alauddin Makassar. Oberholzer, S. (2021). Education as humanitarian response. Graduate Institute of International and Development Studies, Global Obidike, N. D., & Enemuo, J. O. (2013). The role of teachers of young children in ensuring developmentally appropriate practice in early childhood education curriculum implementation. Journal of Emerging Trends in Educational Research and Policy Studies, 4(5), 821. Owusu-Fordjour, C., Koomson, C. K., & Hanson, D. (2020). The impact of Covid-19 on learning-the perspective of the Ghanaian student. European Journal of Education Studies. Palaiologou, I. (2016). Teachers’ dispositions towards the role of digital devices in play-based pedagogy in early childhood education. Early Years, 36(3), 305–321. Punch, K. F. (2013). Introduction to social research: Quantitative and qualitative approaches. sage. Purbo, O. W. (2017). Digital Indonesia: Connectivity and Divergence. In E. Jurriens & R. Tapsell (Eds.), Narrowing the digital divide (pp. 75–92). ISEAS-Yusof Ishak Institute. Putra, A. Y. (2020). Strategi pembelajaran motorik kasar pada anak usia dini era pandemi covid-19. Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 5(4), 159–166. Qualls, N., Levitt, A., Kanade, N., Wright-Jegede, N., Dopson, S., Biggerstaff, M., Reed, C., Uzicanin, A., Levitt, A., Dopson, S., Frank, M., Holloway, R., Koonin, L., Rasmussen, S., Redd, S., de la Motte Hurst, C., Kanade, N., Qualls, N., Rainey, J., Reed, C. (2017). Community Mitigation Guidelines to Prevent Pandemic Influenza — United States, 2017. MMWR. Recommendations and Reports, 66(1), 1–34. https://doi.org/10.15585/mmwr.rr6601a1 Rahiem, M. D. H. (2018). Faith and Disaster Resilience: What can Islamic Education Teach Children to Help Prepare Them for A Disaster? TARBIYA: Journal of Education in Muslim Society, 5(2), 178–192. https://doi.org/10.15408/tjems.v5i2.9964 Rahiem, M. D. H. (2020a). The Emergency Remote Learning Experience of University Students in Indonesia amidst the COVID-19 Crisis. International Journal of Learning, Teaching and Educational Research, 19(6), 1–26. https://doi.org/10.26803/ijlter.19.6.1 Rahiem, M. D. H. (2020b). The Emergency Remote Learning Experience of University Students in Indonesia amidst the COVID-19 Crisis. International Journal of Learning, Teaching and Educational Research, 19(6), 1–26. https://doi.org/10.26803/ijlter.19.6.1 Rahiem, M. D. H. (2021a). COVID-19 and Surge of child marriages: A Phenomena in Nusa Tenggara Barat, Indonesia. Child Abuse & Neglect, 105168. https://doi.org/https://doi.org/10.1016/j.chiabu.2021.105168 Rahiem, M. D. H. (2021b). Indonesian University Students’ Likes and Dislikes about Emergency Remote Learning during the COVID-19 Pandemic. Asian Journal of University Education; Vol 17 No 1 (2021): AJUE Vol 17 No 1 January 2021. https://doi.org/10.24191/ajue.v17i1.11525 Rahiem, M. D. H. (2021c). Storytelling in early childhood education: Time to go digital. International Journal of Child Care and Education Policy, 15(1), 4. https://doi.org/10.1186/s40723-021-00081-x Rahiem, M. D. H., & Husna, K. (2020). Buku Cerita Bergambar Untuk Pembelajaran Mitigasi Bencana Gunung Meletus Bagi Anak Usia Dini. PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 3(2), 54–67. https://doi.org/https://doi.org/10.31849/paud-lectura.v3i02.3974 Rahiem, M. D. H., Krauss, S. E., & Ersing, R. (2021). Perceived Consequences of Extended Social Isolation on Mental Well-Being: Narratives from Indonesian University Students during the COVID-19 Pandemic. In International Journal of Environmental Research and Public Health (Vol. 18, Issue 19). https://doi.org/10.3390/ijerph181910489 Rahiem, M. D. H., & Widiastuti, F. (2020). Pembelajaran Mitigasi Bencana Alam Gempa Bumi untuk Anak Usia Dini melalui Buku Bacaan Bergambar. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1), 36. https://doi.org/10.31004/obsesi.v5i1.519 Rahman, T., & Sharma, U. (2021). A simulation of COVID-19 school closure impact on student learning in Bangladesh. Ransford, C. R., Greenberg, M. T., Domitrovich, C. E., Small, M., & Jacobson, L. (2009). The Role of Teachers’ Psychological Experiences and Perceptions of Curriculum Supports on the Implementation of a Social and Emotional Learning Curriculum. School Psychology Review, 38(4). Reuge, N., Jenkins, R., Brossard, M., Soobrayan, B., Mizunoya, S., Ackers, J., Jones, L., & Taulo, W. G. (2021). Education response to COVID 19 pandemic, a special issue proposed by UNICEF: Editorial review. International Journal of Educational Development, 87, 102485. Robson, C. (2002). Real world research: A resource for social scientists and practitioner-researchers. Wiley-Blackwell. Saldaña, J. (2009). An Introduction to Codes and Coding. The Coding Manual for Qualitative Researchers. https://doi.org/10.1519/JSC.0b013e3181ddfd0a Saldaña, J. (2016). The Coding Manual for Qualitative Researchers (No. 14). Sage. Samuelsson, I. P., & Carlsson, M. A. (2008). The playing learning child: Towards a pedagogy of early childhood. Scandinavian Journal of Educational Research, 52(6), 623–641. Saputri, I. (2019). Konsep Penafsiran Hadits Memuliakan Tamu Terhadap Perilaku Masyarakat Di Kecamatan Besulutu Kabupaten Konawe. Jurnal Ushuluddin Adab Dan Dakwah, 2(1), 42–64. Sar, B. K., & Bledsoe, L. K. (2021). Willingness to intervene in child abuse and neglect: An exploratory study. Child Abuse Review, 30(3), 226–238. Sari, H. N., Maryani, K., & Rusdiyani, I. (2022). Pola Asupan Gizi Anak Usia Dini Pada Masa Pandemi COVID-19. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 7, 51–64. Setyowahyudi, R., & Ferdiyanti, T. (2020). Keterampilan guru PAUD Kabupaten Ponorogo dalam memberikan penguatan selama masa pandemi COVID-19. Jurnal Golden Age, 4(01), 99–111. Shinde, V., Jagtap, N., & Shukla, H. (2021). Deep Learning based Face-Mask and Shield Detection. 2021 International Conference on Computational Intelligence and Computing Applications (ICCICA), 1–4. Singer, E. (2013). Play and playfulness, basic features of early childhood education. European Early Childhood Education Research Journal, 21(2), 172–184. Sserwanja, Q., Kawuki, J., & Kim, J. H. (2021). Increased child abuse in Uganda amidst Covid‐19 pandemic. Journal of Paediatrics and Child Health, 57(2), 188–191. Suhendro, E. (2020). Strategi Pembelajaran Pendidikan Anak Usia Dini di Masa Pandemi Covid-19. Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 5(3), 133–140. Sujarwoto, S., & Tampubolon, G. (2016). Spatial inequality and the Internet divide in Indonesia 2010–2012. Telecommunications Policy, 40(7), 602–616. https://doi.org/10.1016/j.telpol.2015.08.008 Tarricone, P., Mestan, K., & Teo, I. (2021). Building resilient education systems: A rapid review of the education in emergencies literature. Toran, M., Sak, R., Xu, Y., Şahin-Sak, İ. T., & Yu, Y. (2021). Parents and children during the COVID-19 quarantine process: Experiences from Turkey and China. Journal of Early Childhood Research, 19(1), 21–39. Tsolou, O., Babalis, T., & Tsoli, K. (2021). The Impact of COVID-19 Pandemic on Education: Social Exclusion and Dropping out of School. Creative Education, 12(03), 529. UNESCO. (2020). COVID-19 Impact on Education. https://en.unesco.org/covid19 Wang, D., & Fawzi, W. W. (2020). Impacts of school feeding on educational and health outcomes of school-age children and adolescents in low-and middle-income countries: protocol for a systematic review and meta-analysis. Systematic Reviews, 9(1), 1–8. Wendling, J.-M., Fabacher, T., Pébaÿ, P.-P., Cosperec, I., & Rochoy, M. (2021). Experimental efficacy of the face shield and the mask against emitted and potentially received particles. International Journal of Environmental Research and Public Health, 18(4), 1942. Yukich, J., Worges, M., Gage, A. J., Hotchkiss, D. R., Preaux, A., Murray, C., & Cappa, C. (2021). Projecting the impact of the COVID-19 pandemic on child marriage. Journal of Adolescent Health, 69(6), S23–S30. Zylke, J. W., & Bauchner, H. (2020). Mortality and Morbidity. JAMA, 324(5), 458. https://doi.org/10.1001/jama.2020.11761